Removal of Di-n-butyl phthalate from aged leachate under optimal hydraulic condition of leachate treatment process and in the presence of its dominant bacterial strains - Liu, Hongyuan; Li, Hong; Fang, Chengran; Mao, Hongzhi; Xue, Xiangdong; Wang, Qun (Ecotoxicology and environmental safety, 2021)
The effects of hydraulic condition of reactor and the dominant degrading bacteria on the removal of di-n-butyl phthalate (DBP) from aged landfill leachate by anaerobic/anoxic/oxic (A/A/O) leachate treatment process were investigated. The optimal DBP removal (96.0%) was obtained from aged leachate when the hydraulic retention time (HRT) of the reactor was 3 d, internal reflux ratio of the reactor was 200%, and external reflux ratio of the reactor was 60%, respectively. The removal efficiency of DBP was significantly improved after the inoculation of the dominant DBP-degrading bacteria (Pseudomonas sp. W1) in the reactor. The mean removal efficiencies of DBP before and after inoculation were 94.1% and 97.7%, respectively. Furthermore, the inoculation of dominant DBP-degrading bacteria changed the original sludge structure and characteristics, which was more conducive to the removal of DBP. These results provide theoretical basis for the effective removal of DBP from aged leachate by the biological treatment process. [Display omitted] •The optimal HRT of the reactor for DBP removal from aged leachate was 3 d.•The optimal internal and external reflux ratios were 200% and 60% respectively.•The removal efficiency of DBP was significantly improved after inoculation.•The sludge structure and characteristics changed to more conducive after inoculation.